2014
DOI: 10.1016/j.psychres.2014.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and clinical correlates of the Astrand–Rhyming sub-maximal exercise test in patients with schizophrenia or schizoaffective disorder

Abstract: Reliability and clinical correlates of the Astrand-Rhyming sub-maximal exercise test in patients with schizophrenia or schizoaffective disorder, Psychiatry Research, http://dx.doi.org/10.1016/j.psychres. 2014.08.049 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…These changes indicate an important improvement in metabolic and cardiovascular health of the patients and are in line with other studies published on 12-week intervention programs 19,20. Although it has not been tested in depressed patients before, data on patients with schizophrenia indicate that familiarization effects are minimal 21. The increase in fitness, however, was not correlated in any way to changes in kynurenine ( r =−0.11, P =0.32), KYNA ( r =−0.01, P =0.89) or the KYNA/kynurenine ratio ( r =0.11, P =0.44; Figure 1E).…”
Section: Resultssupporting
confidence: 87%
“…These changes indicate an important improvement in metabolic and cardiovascular health of the patients and are in line with other studies published on 12-week intervention programs 19,20. Although it has not been tested in depressed patients before, data on patients with schizophrenia indicate that familiarization effects are minimal 21. The increase in fitness, however, was not correlated in any way to changes in kynurenine ( r =−0.11, P =0.32), KYNA ( r =−0.01, P =0.89) or the KYNA/kynurenine ratio ( r =0.11, P =0.44; Figure 1E).…”
Section: Resultssupporting
confidence: 87%
“…Based on HR at a specific workload (Watt) the oxygen uptake (VO 2 max) was estimated using the Astrand-Rhyming sex-and age-sensitive nomogram. A recent study has proved The AastrandRhyming test as valid and applicable for patients with schizophrenia (Vancampfort et al, 2014).…”
Section: Physical Activitymentioning
confidence: 99%
“…The Astrand-Rhyming protocol is a single-stage cycle ergometer test designed to elicit a steady-state HR for a 6-minute period. Recent research (Vancampfort et al, 2014a) has demonstrated that the Astrand-Rhyming test is a reliable and safe test to measure aerobic capacity of people with schizophrenia. The initial workload was selected from the Astrand test loading wattage table, pedaling speed remained constant (60 revolutions/minute), and HR was recorded at every minute interval.…”
Section: Aerobic Fitnessmentioning
confidence: 99%